PENGARUH PEMANFAATAN ARTIFICIAL INTELLIGENCE ( AI ) TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA PADA SMAN 1 KUPANG TENGAH - Jasmine Gabriella Bait; Yewang, Markus Umbu Kalola; Butar-Butar, Agustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital technology, particularly artificial intelligence, has revolutionized education by making learning more accessible and enhancing understanding. This technology enables students to access a wealth of information and personalized learning experiences, while also breaking down geographic and socioeconomic barriers. However, if misused or over-relied upon, these tools can foster dependency and hinder the development of critical thinking skills. Therefore, it is crucial to balance the integration of technology with traditional teaching methods to maximize benefits and minimize potential drawbacks. Consequently, research is needed to examine the extent to which the use of artificial intelligence (AI) affects student motivation and learning outcomes at SMAN 1 Kupang Tengah. This study employs a quantitative approach with a causal-associative research design. The study population consists of 209 Grade XI students at SMAN 1 Kupang Tengah, with a sample of 137 students selected using Simple Random Sampling based on Slovin's formula. Data collection involved distributing questionnaires to measure the variables of AI usage and learning motivation, alongside the documentation of student grades to obtain data on academic outcomes. Data analysis was conducted using validity tests, reliability tests, prerequisite analysis tests, simple linear regression analysis, t-tests, and the coefficient of determination, utilizing SPSS version 27 software. The research findings indicate that the use of Artificial Intelligence (AI) has a positive and significant impact on students' learning motivation and academic outcomes. Appropriate use of AI can boost enthusiasm for learning, facilitate the understanding of material, expand access to learning resources, and support improved academic performance. Consequently, the research hypothesis is accepted, demonstrating that more effective use of Artificial Intelligence (AI) in learning activities correlates with higher levels of student learning motivation and better academic outcomes. This study is expected to serve as a reference for schools and educators in developing innovative, technology-based learning and in encouraging students to utilize AI wisely, critically, and responsibly.